Kualitas Laporan Keuangan Ditinjau Dari Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Tingkat Pemahaman Akuntansi LPD di Kecamatan Mengwi - Ni Made Novita Dariyanti; Gde Herry Sugiarto Asana; Sarita Vania Clarissa (UNHI Press, 2026)
This research aims to determine the quality of financial reports in terms of human resource competency, information technology utilization, and the level of accounting understanding of LPD in Mengwi District. This type of research is quantitative research using primary data. The data collection technique was through the distribution of questionnaires. The population in this research was 38 LPD in Mengwi District. Sampling used a purposive sampling method with certain criteria. The data analysis technique used was IBM SPSS Statistics Version 25 software, which consists of validity and reliability tests, classical assumption tests, multiple linear regression analysis, model feasibility tests (F tests), partial tests (t tests), and coefficient of determination (R²) tests. The results of this research indicate that (1) Human Resource Competence has a positive and significant effect on the Quality of Financial Reports. (2) The Utilization of Information Technology has a positive and significant effect on the Quality of Financial Reports. (3) The Level of Accounting Understanding has a positive and significant effect on the Quality of Financial Reports.